1983
DOI: 10.1007/bf00116635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allozyme variation on fitness components in Drosophila melanogaster

Abstract: We have explored in Drosophila melanogaster the fitness effccts of allelic variation at three enzyme loci: aGdh, Adh, and Acph. Viability and rate of development are studied at two densities, near-optimal and competitive. No genotypic effects could be demonstrated on rate of development at either density or on viability under optimal conditions. Small but significant effects on viability appear under competitive conditions. Fecundity is measured for all ninc possible mating combinations between the three femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
3
0
0
Order By: Relevance
“…Association between fecundity and genotype was expected to be high, since fecundity is associated with the heterozygosity of allozymes in several organisms, including Mytilus (Rodhouse et al 1986), Drosophila (Serradilla & Ayala 1983) and Pinus 'ponderosa pine' (Linhart & Mitton 1985). Moreover, the correlation between size and fecundity in barnacles and the association between growth and GPI* genotype association in the present study further reinforced this expectation.…”
Section: Fecunditysupporting
confidence: 80%
“…Association between fecundity and genotype was expected to be high, since fecundity is associated with the heterozygosity of allozymes in several organisms, including Mytilus (Rodhouse et al 1986), Drosophila (Serradilla & Ayala 1983) and Pinus 'ponderosa pine' (Linhart & Mitton 1985). Moreover, the correlation between size and fecundity in barnacles and the association between growth and GPI* genotype association in the present study further reinforced this expectation.…”
Section: Fecunditysupporting
confidence: 80%
“…Our results agree with those of the other authors that differences can only be observed under special conditions (Morgan, 1975;Watanabe and Watanabe, 1977;Van Delden et aL, 1978;Serradilla and Ayala, 1983) and that FF homozygotes are more viable than SS ones (Morgan, 1975;Watanabe and Watanabe, 1977;Van Delden et a!., 1978) although Serradilla and Ayala (1983) did not find a significant difference between them. Given the diversity of conditions, these coincidences are noteworthy.…”
Section: Fitness Differences Among Single-locus Genotypessupporting
confidence: 93%
“…The results are shown in Table 6, which gives the number of adult progeny expected for each mating type under the conditions of the experiment. Male underdominance was observed by Serradilla & Ayala (19836) in similar experiments with other loci of D. The male genotypes d o not show overdominance; rather, there is an apparent underdominance at high density, although the effect is small compared to the overdominance of the females.…”
Section: Resultssupporting
confidence: 59%